2015
DOI: 10.1590/0103-166x2015000200006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of theory of mind: A study with students from public and private schools

Abstract: Estudos de Psicologia I Campinas I 32(2) I 213-220 I abril -junho 2015 AbstractThis study assessed the development of the theory of mind in preschool children aged 4 and 5 years old, along with potential interactions among gender, age and whether children were from private or public schools. A total of 178 children (91 students from public schools and 87 from private schools) participated in the study. After securing ethical compliance with applicable guidelines, we applied the Theory-of-Mind-Scale. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
1
1
0
9
Order By: Relevance
“…The understanding of Real–Apparent Emotion seems to be one of those cultural aspects. This has also been shown in previous studies from Japan and Brazil, collectivistic countries according to Hofstede et al (), where tasks pertaining to Real–Apparent Emotion were easier than False Belief (Naito & Seki, ; Rodrigues et al, ). In another collectivistic country, Turkey, the task of Real–Apparent Emotion had to be removed to obtain a scalability of the ToM scale (Etel & Yagmurlu, ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The understanding of Real–Apparent Emotion seems to be one of those cultural aspects. This has also been shown in previous studies from Japan and Brazil, collectivistic countries according to Hofstede et al (), where tasks pertaining to Real–Apparent Emotion were easier than False Belief (Naito & Seki, ; Rodrigues et al, ). In another collectivistic country, Turkey, the task of Real–Apparent Emotion had to be removed to obtain a scalability of the ToM scale (Etel & Yagmurlu, ).…”
Section: Discussionsupporting
confidence: 83%
“…In Iran, just as in China, by what means knowledge is accessed is emphasised in interaction, more so than diverse beliefs and the pattern of ToM development is also similar in Chinese and Iranian children (Shahaeian, Peterson, Slaughter, & Wellman, ). Further, results from Brazil (Rodrigues, Pelisson, Silveira, Ribeiro, & Silva, ) indicated that Real–Apparent Emotion was easier than both False Belief tasks in the scale, and from a Turkish context, Etel and Yagmurlu () reported that they needed to exclude the Real–Apparent Emotion task to achieve satisfactory scalability. In addition, on the basis of other test materials, it has been suggested that Japanese children might master the distinction between real and apparent emotional displays earlier than they solve False Belief tasks (Naito & Seki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considerar essa construção processual corrobora outros achados na literatura (Shahaeian, Peterson, Slaughter, & Wellman, 2011), que argumentam em favor da importância da cultura na constituição do indivíduo e no seu desenvolvimento sociocognitivo. As experiências anteriores das crianças, bem como o contexto sociocultural em que estão inseridas são apontadas em muitos estudos (Deleau, 2012;Morgan, Meristo, Mann, Hjelmquistc, Suriand, & Siegal, 2014;Panciera, 2007;Panciera & Domingues, 2013;Rodrigues, Pelisson, Silveira, Ribeiro, & Silva, 2015) como fatores importantes para o desenvolvimento de uma teoria da mente.…”
Section: Tabela 1 Medidas Descritivas Do Desempenho Nos Instrumentos unclassified
“…Segundo Hadwin et al (1996), as crianças de 18 a 30 meses de idade já conseguem se referir a uma série de estados mentais, como, emoções, desejos, crenças, pensamentos, sonhos e fingimentos. O que mostra a capacidade das crianças dessa idade entenderem que os desejos movem as ações humanas e que os estados mentais não são observáveis ou tangíveis (RODRIGUES et al, 2015).…”
Section: Introductionunclassified
“…Com 5 anos de idade, as crianças apresentam uma compreensão de que os indivíduos podem ter uma emoção interna diferente do que eles expressam em uma determinada situação (RODRIGUES et al, 2015). Essa constatação sugere que a partir dos 5 anos, a habilidade da Teoria da Mente se encontra bem desenvolvida (ROAZZI;SANTANA, 2008).…”
Section: Introductionunclassified